Striving for peace, security, and development of the world annals of Pugwash 1991 - Rotblat, Joseph (World Scientific, 1993)
Covers six themes: world peace; nuclear disarmament issues; arms control; security in the Asia-Pacific region; development strategies and world economic order; energy and the environment. The arguments presented are taken from the scientists and scholars who met at a Pugwash Conference in 1991.